2019
DOI: 10.3390/ani9060304
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Sperm Cryopreservation Protocol for Mediterranean Brown Trout: A Comparative Study of Non-Permeating Cryoprotectants and Thawing Rates In Vitro and In Vivo

Abstract: The aim of our study was to test the effects of different non-permeating cryoprotectants (NP-CPAs), namely low-density lipoproteins (LDLs), sucrose, and egg yolk, and thawing rates on the post-thaw semen quality and fertilizing ability of the native Mediterranean brown trout. Pooled semen samples were diluted 1:3 (v:v) with 2.5%, 5%, 10%, or 15% LDL; 0.05, 0.1, or 0.3 M sucrose; or 10% egg yolk. At the moment of analysis, semen was thawed at 30 °C/10 s or 10 °C/30 s. The post-thaw semen quality was evaluated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
(85 reference statements)
1
16
3
1
Order By: Relevance
“…Other authors also found that a higher thawing temperature ensured better sperm cryosurvival [9,13,15,16]. On the contrary, in our previous research, the thawing temperature of 10 • C registered both a higher post-thaw semen quality and fertilization ability with respect to those recorded at 30 • C/10 s [7]. These conflicting results could be attributed to the different experimental conditions adopted in the two studies (extender composition, freezing rates and equilibration time).…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…Other authors also found that a higher thawing temperature ensured better sperm cryosurvival [9,13,15,16]. On the contrary, in our previous research, the thawing temperature of 10 • C registered both a higher post-thaw semen quality and fertilization ability with respect to those recorded at 30 • C/10 s [7]. These conflicting results could be attributed to the different experimental conditions adopted in the two studies (extender composition, freezing rates and equilibration time).…”
Section: Discussioncontrasting
confidence: 68%
“…The freezing procedure tested here turned out to have a positive impact on sperm total motility post-thawing, recording values above 80%. These results were remarkably better compared to that found in our previous studies, which ranged between 33% and 52% [5][6][7]. However, a significant decrease in the total motility after thawing compared to the fresh semen was recorded, although this is expected following the cryopreservation process.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations